2021
DOI: 10.1021/acs.jpcc.1c01043
|View full text |Cite
|
Sign up to set email alerts
|

System Size-Dependent Transport Properties in Materials of Nanoscale Dimension

Abstract: Fluid transport in finite-sized nanoporous materials is critically affected by apparent interfacial barriers, which severely restrict efficiency improvement on reduction in system size; however, the mechanism leading to this effect even in defect-free materials is unknown. Using large-scale atomistic simulations emulating carbon nanotube (CNT) and zeolite membranes up to a micrometer thick, we demonstrate that transport coefficients in finite nanomaterials are non-uniform and increase with distance from the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(38 citation statements)
references
References 56 publications
(122 reference statements)
5
33
0
Order By: Relevance
“…As a result, the transport coefficient is position-dependent and only matches that of the bulk material beyond a sufficiently large distance, termed the entry length. 23 Hibbe et al 3 alluded to a thin layer of severely decreased diffusivity, consistent with this argument, albeit attributing pore blockage as the underlying cause. While this may be the case for nonideal materials, the existence of the entry region of nonuniform lower diffusivity for ideal materials is suggested by our findings.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…As a result, the transport coefficient is position-dependent and only matches that of the bulk material beyond a sufficiently large distance, termed the entry length. 23 Hibbe et al 3 alluded to a thin layer of severely decreased diffusivity, consistent with this argument, albeit attributing pore blockage as the underlying cause. While this may be the case for nonideal materials, the existence of the entry region of nonuniform lower diffusivity for ideal materials is suggested by our findings.…”
Section: Introductionmentioning
confidence: 78%
“…14,15 However, simulations have shown that interfacial resistance is inherent even to ideal or defect-free materials 7,16−22 due to the symmetry breaking at the surface; nevertheless, the precise mechanisms that lead to the resistance have received limited attention. 23 Further, while its origin is unclear, this interfacial resistance is affected by the interphase interaction between the external environment and the confined fluid, as has been recently demonstrated by us for the gas−zeolite system, 7 with the internal interfacial resistance increasing in the presence of a polymer at the gas−solid interface.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…It is worth noting that the collective behavior of adsorbates on the surfaces, around the pore entrances, and within the pore channels can influence the adsorption, diffusion, and entering processes, but under low pressure, these effects might be insignificant. On the other hand, revealing the decoupled entering process is also quite valuable.…”
Section: Introductionmentioning
confidence: 99%